SISTEM PENGGAJIAN DOSEN UNIVERSITAS BINA DARMA MENGGUNAKAN METODE OOD(OBJECT ORIENTED DESIGN) - Megawaty, Megawaty (Universitas Bina Darma, 2013)
University Bina Darma in the management of payroll data done in 2 ways ie by PHP system to input absence teachers teach and Microsoft Excel system for calculating faculty salaries. Previous use of the system at the University of Bina Darma Palembang (UBD) there are still a lot of errors that occur, among others, were: salaries are calculated by the calculation are not the same as professor of finance because the lecturer did not get a paycheck from the financial, it is felt it is difficult for lecturers. To overcome this, the author intends to create a web-based payroll system using object-oriented methods with the tool design using UML (Unified Modelling Language). Besides, this system will produce a prototyping (modeling) which is the implementation of Web payroll UBD. Keywords:Salary, Apache, dan PHP.